Healthcare Provider Knowledge and Attitudes Regarding Reporting Diseases and Events to Public Health Authorities in Tennessee - Fill, Mary-Margaret A. (J Public Health Manag Pract, 2017)
CONTEXT: In the United States (U.S.), state laws require healthcare providers to report specific diseases and events to public health authorities, a fundamental facet of disease surveillance. However, reporting by providers is often inconsistent, infrequent and delayed. OBJECTIVE: To examine knowledge, attitudes, and practices regarding and understand current barriers to provider disease reporting. DESIGN: A cross-sectional study was conducted via an anonymous, standardized electronic survey. SETTING: The survey was conducted at Vanderbilt University Medical Center, a large, tertiary academic medical center in Nashville, Tennessee. PARTICIPANTS: Healthcare providers in four specialties (internal medicine, pediatrics, obstetrics-gynecology and emergency medicine). MAIN OUTCOME MEASURE(S): Knowledge of and attitudes regarding provider reporting of diseases to public health authorities in Tennessee. RESULTS: The majority of providers acknowledged they cared for patients with reportable diseases (362/435, 83.2%) and believed that it was their responsibility to report to public health authorities (429/436, 98.4%); however less than half had ever reported a case (206/436, 47.2%). The median percent correct on the knowledge assessment of Tennessee reportable diseases and conditions was 81.3% (Interquartile Range [IQR] 68.8–87.5). Providers cited a lack of knowledge of which diseases are reportable (186/429, 43.3%) and the logistics of reporting (153/429, 35.7%) as the primary barriers for compliance. CONCLUSIONS: Most providers acknowledged they cared for patients with reportable diseases and believed they had an obligation to report to public health authorities. However, a lack of knowledge about reporting was frequently described as a limitation to report effectively. Many knowledge deficits were significantly greater among residents than other providers. The policy and practice implications of these findings include a demonstrated need for education of providers about disease reporting as well as development of more convenient reporting mechanisms. Fundamental knowledge of reportable disease requirements and procedures is critical for participation in the broader public health system.